2016
DOI: 10.1088/0957-4484/27/44/445302
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire formation is preceded by nanotube growth in templated electrodeposition of cobalt hybrid nanostructures

Abstract: Cobalt fluted nanowires, novel nanostructures with a diameter of 200 nm consisting of a solid nanowire base and a thin, nanotubular flute shape, were grown in track-etched polycarbonate membranes via templated electrodeposition. The structures were characterized electrochemically via cyclic voltammetry, chronoamperometry, and charge stripping, and structurally via SEM, TEM, and focused ion beam cross-sectioning. Electrochemical and structural analysis reveals details of their deposition kinetics, structure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
4
3
0
Order By: Relevance
“…The observed current loop (crossover) at −0.89 V vs Ag/AgCl indicates that the cobalt deposition occurs via nucleation and growth, in agreement with the results reported in ref . At slower scan rates of 1 or 5 mV/s a notable reduction peak was detected at −0.75 V vs Ag/AgCl, as reported by Dryden et al for Co deposition . By increasing the scan rate a crossover was also observed by the authors, at a similar potential to that reported in this work .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The observed current loop (crossover) at −0.89 V vs Ag/AgCl indicates that the cobalt deposition occurs via nucleation and growth, in agreement with the results reported in ref . At slower scan rates of 1 or 5 mV/s a notable reduction peak was detected at −0.75 V vs Ag/AgCl, as reported by Dryden et al for Co deposition . By increasing the scan rate a crossover was also observed by the authors, at a similar potential to that reported in this work .…”
Section: Resultssupporting
confidence: 92%
“…At slower scan rates of 1 or 5 mV/s a notable reduction peak was detected at −0.75 V vs Ag/AgCl, as reported by Dryden et al for Co deposition . By increasing the scan rate a crossover was also observed by the authors, at a similar potential to that reported in this work . The corresponding oxidation peak from Co 0 to Co 2+ is evidenced at −0.1 V vs Ag/AgCl.…”
Section: Resultssupporting
confidence: 89%
“…However, the growth could not be well-controlled -many deposited structures were just solid wires. A similar behaviour was reported by Dryden et al (2016) for Co, but only with one tube-wire transition located at the end. As shown by both contributors, these structures are very fragile and tend to break at the wire-tube transition.…”
Section: Wire-tube Nanoelementssupporting
confidence: 87%
“…Experimentally, such structures have been prepared by direct electroplating in nanopores or by a related so-called coaxial lithography (Ozel et al 2015). Most works report only one transition, where a tube segment is formed during the initial stage of electroplating (Dryden et al 2016) and its tube wall thickness gradually increases until the growth continues with a solid wire. This was shown, e.g., in case of Co-Pt nanostructures (Arshad et al 2014; diameter 200 nm, tube length about 1 µm).…”
Section: Wire-tube Nanoelementsmentioning
confidence: 99%
“…For film deposition the electrode was constructed with the Au electrode exposed to the solution; for nanowire deposition the non-coated side was exposed to solution, forcing deposition to occur within the pores. An illustration of the sample setup is shown elsewhere [11][12][13].…”
Section: Materials Synthesismentioning
confidence: 99%